Molecular Diversity of Rice Ragged Stunt Oryzavirus in Java and Bali, Indonesia: Molecular Diversity of Rice Ragged Stunt Virus in Indonesia - Kusuma, Asista Fatma; Sulandari, Sri; Somowiyarjo, Soesamto; Hartono, Sedyo (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
ice ragged stunt virus (RRSV), a member of the Genus Oryzavirus in the Family Reoviridae, is one of the most important causal agent of rice viral diseases in Asia. This virus is transmitted by brown planthopper (Nilaparvata lugens) in a persistent manner. It was first discovered in 1967 in Pandeglang, Indonesia that RRSV infects another plant in Gramineae family. The disease incidences were rarely reported in high damage until major outbreak were observed during 2010 to 2011 in several rice growing regions. The purpose of this research was to provide scientific information of RRSV distribution and molecular diversity in Indonesia. About 16 samples with yellowing, ragged and stunting symptoms were collected from Special Region of Yogyakarta, East Java, West Java, Central Java and Bali. PCR assay was used to detect RRSV in samples using specific primer for Coat Protein (CP) gene. The results revealed that 14 out of 16 samples positively reacted with RRSV primers. The positive samples from D.I.of Yogyakarta, Central Java, and Bali were then sequenced, and the results exhibited that all samples from Indonesia had 99% similarity and were closely related to the isolate RRSV from Chanting, China (i.e., Acc.No.HM125546.1) based on the nucleotide and amino acid sequences of CP gene (segment 8)